Political Rights of Ex-Corruptors vis a vis Electoral Integrity in Indonesia - Rusdiana, Shelvi; Hotmaulana Hutauruk, Rufinus; Fitri, Winda; Jaya, Febri (University of Udayana, 2025)
This study investigates the normative inconsistency vis a vis the political rights of ex-corruption convicts and the principle of electoral integrity within the framework of Sustainable Development Goals (SDGs), particularly SDG 16, in Indonesia. The problem addressed centers on whether allowing individuals convicted of corruption to participate as election candidates aligns with democratic values and sustainable governance. While inclusivity is a key component of both democracy and SDG 16, this research critically examines the extent to which such inclusivity may conflict with the imperative of maintaining public trust and ethical standards in political leadership. Employing a normative legal research method supported by a statutory approach, the study analyzes Indonesian legal instruments. The research identifies a significant legal paradox: integrity is mandated for election officials but not for legislative or presidential candidates. This discrepancy raises critical questions regarding the consistency and credibility of Indonesia’s democratic processes. Findings indicate that allowing ex-corruption convicts to run for office undermines public confidence, hampers political regeneration, and dilutes the ethical foundation of electoral integrity. The analysis also reveals that an uncritical application of SDG 16 as a justification for political inclusivity may inadvertently legitimize impunity and erode democratic accountability. The study calls for urgent legal reforms to align candidacy requirements with broader democratic and developmental objectives. By reinforcing integrity as a universal qualification for public office, Indonesia can uphold the principles of justice, restore electoral legitimacy, and promote sustainable political development.